THU0399 The Ankylosing Spondylitis Disease Activity Index (ASDAS) To Assess Disease Activity in Psoriatic Arthritis. (15th July 2016) - Hermann, J.; Husic, R.; Gretler, J.; Haidmayer, A.; Lackner, A.; Graninger, W.B.; Dejaco, C.
Abstract : Background: Psoriatic arthritis (PsA) belongs to the spondyloarthritides and disease activity can be evaluated by the Disease Activity Index for Psoriatic Arthritis (DAPSA) and the Composite Psoriatic Disease Activity Index (CPDAI) 1 . The Ankylosing Spondylitis Disease Activity Score (ASDAS) is a composite disease activity score for ankylosing spondylitis covering peripheral involvement in both versions selected by ASAS international society (ASDASCRP and ASDASESR ) 2 . Objectives: To evaluate the possible importance of ASDASCRP and ASDASESR to assess disease activity in PsA. Methods: In a cross-sectional study patients attending our outpatient clinic and fulfilling CASPAR criteria of PsA underwent a complete rheumatologic assessment to calculate the disease activity score CPDAI and DAPSA for PsA as well as the ASDASCRP and ASDASESR after informed consent was obtained. On the same day a rheumatologist unaware of the clinical status of the patients performed B-mode and power Doppler (PD) sonography of peripheral joints, of tendon sheets and entheses according to the MASEI, and of perisynovial tissue of finger joints. Results were graded semi-quantitatively and sum scores were calculated for PD signals and for pathological B-mode and PD findings together (GLUS, range 0–832). Descriptive statistics were used to summarise the data and correlations were analysed by the Spearman's rank correlation test. Results: 67 of 84 included patients (49 male, 18 female; mean age 51 (SD 12) years; median disease duration 7 years (IQR 4–18) could be evaluated. We found a strong correlation of the DAPSA and CPDAI score and a low but significant correlation of the GLUS and the PD sum score with the ASDASESR and ASDASCRP (table). We observed only a moderate association of the DAPSA with the GLUS (r=0.52, 95%CI 0.32–0.68) and the association of the CPDAI with the GLUS and the PD sum score (r=0.25, 95%CI 0.003–0.47 and r=0.19, 95%CI -0.06–0.42, respectively) was even lower than the correlation of the GLUS and the PD sum score with the ASDASESR and the ASDASCRP . In PsA-patients with clinically defined remission 25.0% of the patients fulfilled the CPDAI and 29.1% the DAPSA remission criteria. However, in patients with clinically defined remission 50.0% and 54.2% fulfilled the ASDASESR and ASDASCRP criteria for inactive disease. Conclusions: This cross-sectional study shows that the ASDAS might also be a valuable tool to measure disease activity and to define clinical remission in PsA. References: Helliwell PS. Assessment of disease activity in psoriatic arthritis. Clin Exp Rheumatol 2015;33:S44–7. Lukas C, Landewe R, Sieper J, Dougados M, Davis J, Braun J, et al. Development of an ASAS-endorsed disease activity score (ASDAS) in patients with ankylosing spondylitis. Ann Rheum Dis 2009;68:18–24. Disclosure of Interest: None declared